Natkusiak (ca. 1885-1947) - Condon, Richard G. (ARCTIC, 1992)
Few Inuit have displayed the same wanderlust and indefatigable spirit of exploration as the Alaskan Inupiat Natkusiak. As Vilhjalmur Stefansson's primary guide and travelling companion on the noted explorer's two major arctic expeditions, the Stefansson-Anderson Expedition of 1908-12 and the Canadian Arctic Expedition of 1913-18, Natkusiak logged thousands of miles by foot, ship and dog sled. While Stefansson provides few details of Natkusiak's personal life, his voluminous works do contain frequent passages of praise for his companion. In Stefansson's first major publication, My Life with the Eskimo (1913), the author compliments Natkusiak as one of the best Eskimo hunters he has ever known (p. 151), as an individual with the spirit of an adventurer and investigator (p. 155), and as an extremely competent man in everything that concerns making a living in the Arctic (p. 339). In September 1911, when Anderson brought news that Natkusiak had temporarily left the service of the Stefansson-Anderson Expedition, Stefansson wrote: "This was a very disappointing piece of news, for in all my long travels and in everything of difficulty which I had had to undertake in the past three years, Natkusiak had always been my mainstay and in many cases the only man on whom I could rely" (p. 339). [This profile pays tribute to a great Inuit explorer.]